2012
DOI: 10.4103/0972-124x.99268
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge augmentation using chin bone graft, bovine bone mineral, and titanium mesh: Clinical, histological, and histomorphomtric study

Abstract: Background:Resorption of the alveolar ridge often leaves insufficient bone volume. Very few studies have investigated the quantity and quality of bone formation in humans, following alveolar ridge augmentation, using autogenous bone and bovine bone mineral (BBM) under titanium mesh.Materials and Methods:Sixteen alveolar bone defects divided into two groups; control group with symphyseal autogenous bone covered by titanium mesh; and test group with symphyseal autogenous bone mixed with BBM in 1: 1 ratio and cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Patient was cooperative and did not have any relevant medical history , the entire treatment plan was explained to the patient and a consent form was signed. Clinical and radiographic examination revealed limited vertical alveolar ridge height in relation to 16,17,18. Direct maxillary sinus lifting was done by lateral approach with autogeneous symphyseal bone grafting followed by implant placements, suture removal was done after one week ,patient was DOI: 10.9790/0853-1508038187 www.iosrjournals.org 82 | Page recalled for check up at monthly intervals followed by abutment placement and final prosthesis at the end of six months.…”
Section: Case Presentationmentioning
confidence: 99%
“…Patient was cooperative and did not have any relevant medical history , the entire treatment plan was explained to the patient and a consent form was signed. Clinical and radiographic examination revealed limited vertical alveolar ridge height in relation to 16,17,18. Direct maxillary sinus lifting was done by lateral approach with autogeneous symphyseal bone grafting followed by implant placements, suture removal was done after one week ,patient was DOI: 10.9790/0853-1508038187 www.iosrjournals.org 82 | Page recalled for check up at monthly intervals followed by abutment placement and final prosthesis at the end of six months.…”
Section: Case Presentationmentioning
confidence: 99%
“…(3,4) Several studies have successfully used bone filling materials in combination with a titanium mesh for ridge augmentation, but these techniques have many limitations (5)(6)(7)(8)(9) including the exposure of the titanium mesh after surgery, a high rate (up to 52%) of soft tissue dehiscence (5,7) and bone loss due to infection. The complications associated with the titanium mesh appeared to occur regardless of the kind of bone filling material used in combination.…”
Section: Introductionmentioning
confidence: 99%
“…The complications associated with the titanium mesh appeared to occur regardless of the kind of bone filling material used in combination. Alveolar bone defects were treated with symphyseal autogenous bone mixed with or without bovine bone mineral in 1:1 ratio and covered by titanium mesh (8) . The titanium mesh completely exposed in 25 % of the treated defects 1-2 months postoperatively, and then it was removed.…”
mentioning
confidence: 99%
“…The materials used for alveolar bone regeneration (ABR) in the oral cavity include various bone grafts . Bovine bone (BB) xenografts are commonly used in intraoral procedures, with high success rates . In 2004, Hui Xu et al.…”
mentioning
confidence: 99%
“…1 Bovine bone (BB) xenografts are commonly used in intraoral procedures, with high success rates. [2][3][4][5] In 2004, Hui Xu et al showed in a rabbit model that slowly resorbed deproteinized bone particles contribute to stable augmentation of the maxillary sinus by inhibiting bone resorption. 6 A case report by Sartori et al presented histomorphometric data from a 10 year post ABR follow-up with bovine bone and found that the BB particles were in close proximity to the lamellar bone, without signs of graft resorption.…”
mentioning
confidence: 99%